The Effect of Think Pair And Share on Student Participation and Learning Outcomes in Economic Subjects at SMA Negeri 2 Surakarta - Dewi, Nadya Putri; Noviani, Leny (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
The purpose of this research is to compare the effect of implementing the Think Pair and Share (TPS) learning model and the Share (S) model on student participation and learning outcomes in Economics subjects at SMA Negeri 2 Surakarta. The student participation variable used indicators of shyness, state anxiety, students who raise their hands, students who don’t raise their hands, liking with peers and teacher, and the classroom environment. This research used is experimental research method with a cross-over design. The population in this research is class X students at SMA Negeri 2 Surakarta, total 359 students using a random sampling technique with lottery. The number of samples used in this research is 71 students. The data analysis technique used is SPSS version 25 and Anbuso 8.0, while the data collection techniques used in this research are observation techniques, questionnaires distributed used by Google Form, and tests. The results of the study concluded that there was a higher influence on the application of Think Pair and Share (TPS) than Share (S) on student participation and learning outcomes in Economics subjects at SMA Negeri 2 Surakarta, seen from the large percentage of indicators in the application of the Think Pair and Share (TPS) model compared to the Share (S) model and the average score also the number of students who have completeness scores in the Think Pair and Share (TPS) model are greater than the Share (S) model.